Adverse lifestyle and health-related quality of life: gender differences in patients with and without chronic conditions. Issue 2 (March 2016) - Põlluste, Kaja; Aart, Annika; Kallikorm, Riina; Kull, Mart; Kärberg, Kati; Müller, Raili; Ots-Rosenberg, Mai; Tolk, Anni; Uhlinova, Jana; Lember, Margus
Objectives : The aim was to investigate the relationship between the main lifestyle-related factors and health-related quality of life (HRQoL) in a sample of patients with and without chronic conditions (CCs) with respect to the gender differences in both groups. Methods : A cross-sectional study was conducted on 1061 patients (of which 308 had no CCs and 753 of those had one or more CCs) recruited at primary health care centres and the Internal Medicine Clinic at Tartu University Hospital in Estonia. Data were collected during 2012–2014. The patient's age, self-reported smoking status, alcohol consumption (assessed by Alcohol Use Disorders Identification Test) and body mass index were used as independent variables to predict the physical component scores (PCS) and mental component scores (MCS) of HRQoL (assessed by SF-36). Results : Smoking had a negative association with both physical and mental components of HRQoL only in women with CCs. Further, the PCS of chronically ill women was negatively associated with the higher body mass index. Harmful drinking had a negative association with the HRQoL in all patient groups, except with the PCS in women with CC. Light alcohol consumption without symptoms of harmful use or dependency had a positive association with the physical and mental HRQoL in all patient groups, except with the MCS in women without CCs. Conclusion : Adverse lifestyle had the most expressed association with HRQoL in women with CCs. Light alcohol consumption had a positive association, but harmful use of alcohol had an inverse association with HRQoL irrespective of patients' gender or health status.